(untitled) (Coventry Open Press, 2026)
This research examines the rapid rise and societal impacts of generative and agentic artificial intelligence (AI) from a resilience perspective. UK government policy recognises that AI is a “chronic risk” included in the National Risk Register, and that the volunteer, community and faith sector (VCFS) are essential partners in resilience. It places a particular focus on the widespread, unknown nature of impacts hence requiring an “all hazards”, “whole of society”, and social and behavioural sciences-informed approach to anticipating and preparing for such risks. This research makes a significant contribution to a nuanced understanding of a key resilience partner, the faith sector, and its understanding of AI as a societal risk. This foundational study combined desk-based research with primary data from 28 interviews with religious leaders from all major religious faiths in the UK. The results reveal a sector that has, in many cases, thought deeply about the unseen implications of AI, its potential impacts on individual and social psychology, spiritual belief and practice, environmental and political impacts, and religious and theological shifts. It reveals a technological shift that is pushing faith and religious practice into new, unknown territory and that different faith groups are responding in different ways, but also the potential for an interfaith framework based on universal ideals of human dignity, community, and caring for the vulnerable and marginalised. While recognising the potential efficiency gains of such technology, interviewees also expressed a distrust of “big tech” and ethical unease toward the unseen societal, psychological and theological shifts that accompany such technological advances. The project develops new terminology and theory to understand the impacts and frame our understanding and public debate around generative and agentic AI.